KEPUASAN KAPTEN PILOT DAN CO PILOT TERHADAP KINERJA FLIGHT OPERATION OFFICER - Cecep Pahrudin; Adi Chandra; Tito Warsito (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
PT. Sriwijaya Air is one of the national airline was established on November 10, 2003. The paper  purpose is to analyze the degree of correspondence between the performance of flight services operations officer with customer expectations (pilot) PT. Sriwijaya Air, using qualitative methods, while data analysis using the five-dimensional approach, and Cartesian diagram. The analysis shows the level of implementation of quality of service with the average performance of 4.42. Level expectations or interests of customers / pilot average of 4.69, which means that the service performance of flight operations officer told the pilots are considered very important to be well run. At the level of concordance between the implementation of services to the benefit of customers amounted to 94.19%, based on the interpretation table can be interpreted pilots are very satisfied with the performance of flight operations officer PT. Sriwijaya Air.